2010
DOI: 10.1590/s0100-06832010000200024
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest nitrous oxide emissions from a subtropical oxisol as influenced by summer crop residues and their management

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
5
17
1
5
Order By: Relevance
“…In contrast, Escobar et al (2010) concluded that after the harvest, cumulative soil N 2 O emissions from soybean ecosystems were higher in the no-tillage treatment compared with the conventional tillage treatment. Escobar et al (2010) argued that the increased soil moisture in the no-tillage treatment increased the amount of denitrifying activity and consequent N 2 O production. Other studies have found no significant effect of tillage on N 2 O production from soybean crops (Parkin and Kaspar 2006;Jantalia et al 2008).…”
Section: Tillagementioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, Escobar et al (2010) concluded that after the harvest, cumulative soil N 2 O emissions from soybean ecosystems were higher in the no-tillage treatment compared with the conventional tillage treatment. Escobar et al (2010) argued that the increased soil moisture in the no-tillage treatment increased the amount of denitrifying activity and consequent N 2 O production. Other studies have found no significant effect of tillage on N 2 O production from soybean crops (Parkin and Kaspar 2006;Jantalia et al 2008).…”
Section: Tillagementioning
confidence: 88%
“…Some research has been conducted into the effects of residue removal and/or incorporation of crop residues into soils on postharvest N 2 O emissions. However, the results of these studies exploring residue management options were extremely varied (e.g., Malhi et al 2006;Delgado et al 2010;Escobar et al 2010). A recent study focusing on the biotechnology has suggested that the use of the enzyme that reduces N 2 O has a crucial role in reducing atmospheric N 2 O levels (Richardson et al 2009).…”
Section: A New Methods For Mitigation Of Postharvest N 2 O Emissions Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the N fertilizer efficiency is increased Singh et al, 2006;Li et al, 2010), promoting higher economic revenue at a lower environmental impact (Gregoret et al, 2006). When N fertilization rates exceed the crop demand, they can increase the soil N-NO 3 -content and therefore increase the risk of N losses through denitrification (Fernandes & Libardi, 2007;Escobar et al, 2010) or leaching (Sangoi et al, 2003;Ceretta et al, 2005;Fernandes & Libardi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A quantidade de N 2 O produzido em sistemas agrícolas é determinada pela disponibilidade de NO 3 - (Bouwman, 1996;Brown et al, 2000;Maggiotto et al, 2000), temperatura (Castaldi, 2000), pH (Daum & Schenk, 1998;Mogge et al, 1999), umidade (Zheng et al, 2000;Dobbie & Smith, 2003), além do material orgânico prontamente decomponível e das condições limitantes de difusão de O 2 (Mosier et al, 1991 Nesse contexto, o crescimento do setor agropecuário com a conversão da vegetação nativa em diferentes formas de uso da terra, é necessário conhecer as fontes emissoras dos GEE a fim de colaborar com um diagnóstico mais exato para as tomadas de decisões mitigadoras do aquecimento global. Contudo, a maioria dos estudos envolvendo o fluxo desses gases do solo para a atmosfera estão concentrados na região Sul do Brasil, comparando sistemas de cultivos (La Scala Junior et al, 2001;Costa et al, 2008a;Jantaia et al, 2008;Barreto et al, 2009;Gomes et al, 2009;Siqueira Neto et al, 2009;Escobar et al, 2010) e o fluxo de CH 4 em cultivos de arroz irrigado por inundação (Agostinetto et al, 2002;Costa et al, 2008b), assim como na Amazônia, comparando a transição floresta-pastagem (Steudler et al, 1996;Mellilo et al, 2001;Garcia-Montiel et al, 2002;Fernandes et al, 2002;Passianoto et al, 2003;Carmo et al, 2005;Neill et al, 2005;Wick et al, 2005).…”
Section: Introductionunclassified